2020
DOI: 10.1097/ccm.0000000000004605
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Hyponatremia in Patients With Coronavirus Disease 2019 in New York City

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
110
7
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(138 citation statements)
references
References 29 publications
16
110
7
5
Order By: Relevance
“…32 Some studies have shown that the majority of COVID-19 cases have electrolyte abnormalities correlated with a high risk of intensive care needs, mechanical ventilation and encephalopathy events with high mortality rates and longer treatment days. 33,34 Comparable to some other studies, most cases found that most cases had hyponatremia (55.6%). Tezcan, et al mentions that hyponatremia is the most common electrolyte abnormality compared to other electrolyte abnormalities.…”
Section: Discussionsupporting
confidence: 59%
“…32 Some studies have shown that the majority of COVID-19 cases have electrolyte abnormalities correlated with a high risk of intensive care needs, mechanical ventilation and encephalopathy events with high mortality rates and longer treatment days. 33,34 Comparable to some other studies, most cases found that most cases had hyponatremia (55.6%). Tezcan, et al mentions that hyponatremia is the most common electrolyte abnormality compared to other electrolyte abnormalities.…”
Section: Discussionsupporting
confidence: 59%
“…Potential TME etiologies were identified a priori and included the following: electrolyte abnormalities (hyponatremia or hypernatremia, hypoglycemia or hyperglycemia, hypocalcemia or hypercalcemia, hypomagnesemia or hypermagnesemia, or hypophosphatemia or hyperphosphatemia; acidosis/acidemia; or alkalosis/alkalemia), organ failure (renal failure/uremia, liver failure, or pulmonary failure [including hypoxemia or hypercarbia]), hypertensive encephalopathy, sepsis or active infection (from either SARS-CoV-2 or another infection), fever, nutritional deficiency (Wernicke encephalopathy, vitamin B 12 deficiency, or niacin deficiency), or environmental injury (hypothermia or exposure or poisoning) [ 7 , 13 ]. Hypoxic-ischemic encephalopathy (HIE) (also known as anoxic or hypoxic brain injury) was defined as a global cerebral insult due to oxygen deprivation to the brain or lack of perfusion to the brain caused by systemic hypoxemia, hypotension, or cardiac arrest [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have identified neurological events in the context of recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [1][2][3][4][5][6][7][8]. Many of these complications are sequelae of severe illness or represent secondary effects of multisystem organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 virus encephalitis also has been described [ 3 , 4 ]. Unsurprisingly, SIADH-related hyponatremia has been identified in patients hospitalized for COVID-19 [ 5 7 ]. Observational studies have noted an association between interleukin (IL)-6 levels and hyponatremia and suggest that IL-6-mediated inflammation and non-osmotic antidiuretic hormone (ADH) release is the underlying pathophysiology [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, SIADH-related hyponatremia has been identified in patients hospitalized for COVID-19 [ 5 7 ]. Observational studies have noted an association between interleukin (IL)-6 levels and hyponatremia and suggest that IL-6-mediated inflammation and non-osmotic antidiuretic hormone (ADH) release is the underlying pathophysiology [ 7 , 8 ]. Given that brain imaging was normal in our patient, we ruled out direct CNS involvement with SARS-CoV-2 as a cause of encephalopathy.…”
Section: Introductionmentioning
confidence: 99%